TORAKOTOMİLERDE İNDÜKSİYON ÖNCESİ VE SONRASI İNTERPLEVRAL YOLLA UYGULANAN MORFİNİN İZOFLORAN GEREKSİNİMİNE ETKİSİ - EROLÇAY, Hülya; YÜCEYAR, Lale; İPEK, Neval and AYKAÇ, Bora (Cerrahpaşa Medical Journal, 2019)
Background.- Morphine injected interpleurally produces antinociceptive effects, which are mediated by opioid receptors located on intercostal nerves. This study investigates the effect of interpleural morphine on intraoperative isoflorane requirements. Design.- Twenty patients scheduled to thoracotomy were randomly allocated to two goups to receive interpleural morphine before or after the induction of anaesthesia. Systolic, diastolic and mean arterial pressures, hearth rate, Sp02, ETC02, and end-tidal isoflorane concentrations were recorded at 5 min. intervals. In the 1st group 0.3 mg/kg morphine was injected interpleurally using a 'Touhy' needle 30 minutes before the anaesthetic induction. In the 2nd group after the anaesthetic induction operating lung was collapsed by applying one lung ventilation to the dependent lung using double-lumen endotracheal tube and the same dose of morphine was injected with a standard injector. Surgical incision was allowed 30 minutes after the injection. Anaesthetic depth was evaluated with PRST score (blood pressure, pulse rate, sweating, tear formation). Isoflorane concentration was titrated depending upon the same score and also increased or decreased in order to keep mean blood pressure within 10% of baseline values. Anaesthesia was induced with thiopental and atracurium and maintained with isoflorane 02f Air. Atracurium was used to maintain surgical relaxation. Following thoracotomy dependent lung was ventilated with IPPV (intermittent positive pressure ventilation) and operated lung was with HFN (high frequency jet ventilation). In both groups statistical evaluations were performed in the following periods: The period before incision: 1, retraction of ribs: 2, period of IPPV+HPJV: 3, period of IPPV: 4. Comparison of mean end-tidal isoflorane concentrations of two groups was performed using Student's t-test and p<0.05 was considered significant. Results.- There was no significant difference between the two groups (p>0.05). Conclusion.- Administration of interpleural morphine before or after the induction of anaesthesia did not alter intraoperative isoflorane requirements. These observations suggest that morphine is effective on suppressing the stress response in both methods. It is concluded that giving morphine after induction of anaesthesia may be preferred as it is applied under general anaesthesia and so less traumatic to the patients.